A-Equistatistical Convergence of Positive Linear Operators - Aktuglu, Hueseyin; Ozarslan, Mehmet Ali; Gezer, Halil (Eudoxus Press, Llc, 2010)
Recently, the concept of equistatistical convergence which is stronger than statistical uniform convergence was introduced by Balcerzac, Dems and Komisarski. In the present paper we introduce the concept of A-equistatistical convergence which extends equi-statistical convergence. Moreover, we construct examples to show that A-equistatistical convergence lies between A-statistically pointwise and uniform convergence. We also obtain A-equistatistical case of Korovkin result and finally we compute the rates of A-equistatistical convergence of sequences of positive linear operators.
Keywords: Statistical convergence; A-statistical convergence; equi-statistical convergence; Korovkin type approximation theorem; modulus of coutininuity; Bernstein polynomials